Sex and age differences in the association between sympathetic outflow and central elastic artery wall thickness in humans - Holwerda, Seth W; Luehrs, Rachel E; DuBose, Lyndsey E; Majee, Rumbidzai; Pierce, Gary L (American journal of physiology. Heart and circulatory physiology, 2019)
Aging is characterized by increased wall thickness of the central elastic arteries (i.e., aorta and carotid arteries), although the mechanisms involved are unclear. Evidence suggests that age-related increases in muscle sympathetic nerve activity (MSNA) may be a contributing factor. However, studies in humans have been lacking. Therefore, we tested the hypothesis that age-related increases in MSNA would be independently associated with carotid artery intima-media thickness (IMT) but not in young women given the reduced influence of MSNA on the vasculature in this group. In 93 young and middle-age/older (MA/O) adults (19-73 yr, 41 women), we performed assessments of MSNA (microneurography) and common carotid IMT and lumen diameter (ultrasonography). Multiple regression that included MSNA and other cardiovascular disease risk factors indicated that MSNA ( = 0.002) and 24-h systolic blood pressure (BP) ( = 0.024) were independent determinants of carotid IMT-to-lumen ratio (model R = 0.38, < 0.001). However, when examining only young women (<45 yr), no correlation was observed between MSNA and carotid IMT-to-lumen ratio ( = 0.01, = 0.963). MSNA was significantly correlated with IMT-to-lumen ratio while controlling for 24-h systolic BP among young men ( = 0.49, < 0.001) and MA/O women ( = 0.59, = 0.022). However, among MA/O men, controlling for 24-h systolic BP attenuated the association between MSNA and carotid IMT-to-lumen ratio ( = 0.50, = 0.115). Significant age differences in IMT-to-lumen ratio between young and MA/O men ( = 0.047) and young and MA/O women ( = 0.023) were removed when adjusting for MSNA (men: = 0.970; women: = 0.152). These findings demonstrate an association between higher sympathetic outflow and carotid artery wall thickness with a particular exception to young women. Increased wall thickness of the large elastic arteries serves as a graded marker for cardiovascular disease risk and progression of atherosclerosis. Findings from the present study establish an independent association between higher sympathetic outflow and carotid artery wall thickness in adults with an exception to young women and extend findings from animal models that demonstrate hypertrophy of vascular smooth muscle following chronic sympathetic-adrenergic stimulation.